Konsep Pendidikan Islam Zakiah Daradjat Berbasis Kesehatan Mental: Zakiah Daradjat’s Concept of Islamic Education Based on Mental - Fairuz Rahmania Zakkiya; Moch. Bahak Udin By Arifin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mental health has become a critical concern in contemporary society, particularly among younger generations facing rapid digital transformation. Specific Background: Islamic education offers a holistic framework integrating spiritual, moral, and intellectual dimensions that address psychological well-being. Knowledge Gap: Despite extensive discourse on Islamic pedagogy and mental health, limited studies synthesize classical Islamic educational thought with current mental health challenges in the digital era. Aims: This study aims to analyze the conceptual relationship between Islamic education and mental health development through a library research approach grounded in authoritative Islamic scholarship. Results: The findings indicate that Islamic education emphasizes spiritual cultivation, character formation, moral discipline, and balanced personality development as foundational elements for psychological stability. Thinkers such as Zakiah Daradjat highlight the role of faith, worship, and ethical guidance in fostering inner peace and resilience. Novelty: The study presents an integrative conceptual synthesis linking classical Islamic educational principles with contemporary mental health discourse. Implications: The framework provides theoretical guidance for developing education models that support psychological well-being through spiritual and moral foundations within Islamic educational contexts. Keywords: Islamic Education, Mental Health, Spiritual Development, Character Formation, Library Research Key Findings Highlights: Islamic pedagogy integrates spiritual and moral dimensions to support psychological stability. Faith-based guidance contributes to inner balance and resilience. Classical scholarship remains relevant to contemporary psychological challenges.